Synthesis and Preliminary Evaluation of Novel Bone-targeting NSAIDs Prodrugs based on Glutamic Acid Oligopeptides - Zhao, Yi; He, Dongsheng; Ma, Lifang; Guo, Li (Letters in Drug Design & Discovery, 2015)
Osteoarthritis is no doubt a difficult disease to manage. Targeted delivery of drugs to bone may not only enhance the treatment efficacy, but also reduces the quantity of drug administered. In this paper, we have synthesized two series of NSAID-Glu oligopeptide conjugates built up by the therapeutic moiety (naproxen and ibuprofen) and the targeting moieties (Glutamic oligopeptides) via amide linkage, as novel potential bone-targeting NSAIDs prodrugs. Preliminary studies indicated that these prodrugs exhibited outstanding hydroxyapatite affinity, furthermore, NSAIDs-glutamic hexa-peptide conjugates were found more potent in hydroxyapatite binding. The adequate chemical stability of the conjugates in different buffers, indicated that the conjugates might become a promising approach of selective delivery of drugs to bone tissues. These results may be conducive to the study of bone targeting drugs delivery.
Keywords: glutamic acid oligopeptide